Efeito do plasma rico em plaquetas e de plaqueta rica em fibrina na regeneração de lesões com perda de substância do nervo ciático em ratos - Lichtenfels, Martina (2012)
Objective: This study evaluates the effect of Platelet Rich Plasma (PRP) and Platelet Rich Fibrin (PRF) on peripheral nerve repair, comparing the results to the gold-standard (autologous nerve graft) and to the control group with saline solution. Materials and Methods: Thirty six Wistar rats were used in the study, and four of these were blood donors to obtain the PRP and the PRF. The Injuries were made on the sciatic nerve from the left paw with 10mm long gap and they were repaired with one of the four treatments: Autologous nerve grafts (ANG); tubulization with saline solution (TS); tubulization with PRP; tubulization with PRF. Walking track analysis were performed at pre-operative period, 30, 60 and 90 days after surgery. On the 90 postoperative day, the rats were euthanized and histomorphometric analysis were made measuring the fiber diameter, axonal diameter and the myelin sheath thickness. Results: On 90 days post-operative, the ANG, PRF and PRP groups presented a significant functional improvement in relation to the TS group (p = 0.000), which showed functional deficit. On the histomorpometric test, the ANG group presented a better structural organization, with a regular distribution among the myelinated fibers, and little conjunctive tissue between the fibers. The TS, PRP and PRF groups had a larger endoneural tissue between the nerve fibers and presented degenerative process. The ANG group achieved a larger nerve fiber diameter at the proximal segment while comparing with the TS (p = 0.037), and also comparing with the PRF (p = 0.001) and the PRP (p = 0.002) while analyzing the medial segments. About the axonal diameter and the myelin sheath thickness, no statistical significant difference has been found between the groups. Conclusion: This research data suggests that PRP and PRF have positive effects on functional nerve recovery, presenting results similar to the ANG group. However, the PRP and PRF don t achieve a significant improvement on the histomorphometric analysis.